Utilization of Sodium Hydroxide (Naoh) to Treat Used Tyres as Sand Partial Replacement in Engineered Cementitious Composites - Abdul Aziz, A.; Rosli, M. I. F.; Dora, A. G. Kay; Zakaria, N.; Jafri, N. A. (International Journal of Integrated Engineering, 2022)
Engineered cementitious composites (ECC) is distinct for the tensile strain-hardening behaviour and tensile ductility contrasting to the quasi-brittle nature of ordinary concrete. The blended materials of ECC only consist of cement, sand, water, fibre, and admixture. The depleting and limited resources of sand in many countries have led to the research on alternative materials to replace sand partially or fully in the concrete mixture. Therefore, this study aims to utilize the crumb rubber (CR) in ECC as a partial sand replacement to enhance the ductility and energy dissipation capacity of the composite. The additional of CR in the ECC cause reduction of compressive strength of the composites due to its smooth surface resulting to less bonding with cement matrix. Hence, the CR is being treated with 10% sodium hydroxide (NaOH) to improve its surface roughness and enhance the adhesion between CR and cement matrix in the composites. The compressive strength results for ECC contained CR treated for duration of 2 days and 4 days were recorded. Two days is the optimum duration of CR treatment using 10% sodium hydroxide (NaOH) to lessen the reduction of the compressive strength of the rubberized engineered cementitious composites (R-ECC).